Control system for uncoiler with induction motor drive - Mrozek, Bogumiła (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents results of an investigation into the control systems of uncoiler drives in the environment of a rolling mill at metallurgical plant. Variable diameter and variable inertia of coil and demand of stable stretch are important features of this machine. Control system of an uncoiler working without the need of a stretch sensor is presented.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka